2011
DOI: 10.1186/1471-2407-11-303
|View full text |Cite
|
Sign up to set email alerts
|

Glioblastoma-derived Leptin Induces Tube Formation and Growth of Endothelial Cells: Comparison with VEGF Effects

Abstract: Background: Leptin is a pleiotropic hormone whose mitogenic and angiogenic activity has been implicated in the development and progression of several malignancies, including brain tumors. In human brain cancer, especially in glioblastoma multiforme (GBM), leptin and its receptor (ObR) are overexpressed relative to normal tissue. Until present, the potential of intratumoral leptin to exert proangiogenic effects on endothelial cells has not been addressed. Using in vitro models, we investigated if GBM can expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 72 publications
0
54
1
1
Order By: Relevance
“…Using our in vitro co-culture cell model, it was found that leptin did not alter tubule formation when VEGF was lacking but, addition of complete EGM-2 medium supplemented with VEGF did further increase tubule formation. These results are in contrast with the pro-angiogenic effect of leptin (10, 100 and 1000 ng/ml) on endothelial tube formation previously described in single-cell conditions using HUVECs and a matrigel matrix (25)(26)(27) or, HUVECs and a collagen I matrix (28); suggesting that the system used for studying angiogenesis in vitro might be critical even if the use of in vitro co-culture systems are more closely related to in vivo conditions. This study is also the first to use an in vitro endothelial cell/fibroblast co-culture cell system to investigate the effect of combining exogenous cytokines/adipokines.…”
Section: Discussioncontrasting
confidence: 96%
“…Using our in vitro co-culture cell model, it was found that leptin did not alter tubule formation when VEGF was lacking but, addition of complete EGM-2 medium supplemented with VEGF did further increase tubule formation. These results are in contrast with the pro-angiogenic effect of leptin (10, 100 and 1000 ng/ml) on endothelial tube formation previously described in single-cell conditions using HUVECs and a matrigel matrix (25)(26)(27) or, HUVECs and a collagen I matrix (28); suggesting that the system used for studying angiogenesis in vitro might be critical even if the use of in vitro co-culture systems are more closely related to in vivo conditions. This study is also the first to use an in vitro endothelial cell/fibroblast co-culture cell system to investigate the effect of combining exogenous cytokines/adipokines.…”
Section: Discussioncontrasting
confidence: 96%
“…In addition to increasing the proliferation of endothelial cells [27,28,45,85], leptin also caused the proliferation of fibroblasts [86] and diverse malignant cells. In these cells, leptin induced pro-angiogenic, inflammatory and mitogenic actions that were reinforced through crosstalk with several cytokines/growth factors [11,31,87].…”
Section: Leptin’s Impact On Tumor Angiogenesismentioning
confidence: 99%
“…Leptin produced by adjacent adipose might provide a local increased level of stimulation to tumors 6062 , suggesting the presence of tumor associated adipose represents an important microenvironmental influence. Although normally secreted from adipose, self-sufficiency for leptin has recently been shown to be secreted from glioblastoma and breast cancer cells 63, 64 . Further, intra-tumoral mRNA leptin levels in patients with high leptin receptor levels correlated with decreased relapse-free survival 55 .…”
Section: Introductionmentioning
confidence: 99%